2011
DOI: 10.1080/10632913.2011.592469
|View full text |Cite
|
Sign up to set email alerts
|

Contemplating a Constructivist Stance for Active Learning within Music Education

Abstract: This article examines constructivist philosophies for learning with an emphasis on studentcentered environments in education and the active involvement of students in learning as they relate new understanding to what they already know and refine previous skills in terms of newly acquired proficiencies. Active learning is explored from a constructivist perspective in which students adopt an analytic approach to questioning and problem solving. Through these processes, students extend their current understanding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
18
0
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 18 publications
1
18
0
4
Order By: Relevance
“…Öğrenenler çevreleri ile etkileşime girdiklerinde, mevcut bilişsel yapılarına uyan fikirleri benimser veya özümserler ve önceden bildikleri yapılara uymayan fikirleri de değiştirirler veya düzenlerler (Scott, 2011).…”
Section: Introductionunclassified
“…Öğrenenler çevreleri ile etkileşime girdiklerinde, mevcut bilişsel yapılarına uyan fikirleri benimser veya özümserler ve önceden bildikleri yapılara uymayan fikirleri de değiştirirler veya düzenlerler (Scott, 2011).…”
Section: Introductionunclassified
“…Earlier research has shown that using active learning methods increases positive attitudes and students' interest in the subject, motivates active participation in learning activities, increases intrinsic motivation, makes students more active and creative, develops collaboration and social skills, develops self-management skills and critical thinking abilities and creates an active, engaging, exploring-discovering learning environment (e.g. Kährik, Leijen & Kivestu, 2012;RenterReintamm, 2006;Scott, 2010;2011).…”
Section: Introductionmentioning
confidence: 99%
“…Active learning methods are an integral part of modern education, including music education (see for example Brown, 2008;Kährik, Leijen & Kivestu, 2012;Scott, 2010;2011). Use of active learning methods helps to develop a person who is active, energetic, able to collaborate and think creatively while being empathetic, respectful towards others and willing to collaborate in both small and large groups (Kuurme & Siim, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…e.g. Brown, 2008;Kährik, Leijen & Kivestu, 2012;Scott, 2010;2011). When using active learning methods "the pupils will employ an analytical approach to answer questions and solve problems".…”
Section: Introductionmentioning
confidence: 99%
“…
AbstractContemporary pedagogies of musical instruments stress the importance of active and reflective learning (Brown 2008, Scott 2011. However, a model for supporting students' reflection in this context is currently missing.
…”
mentioning
confidence: 99%